PENGGUNAAN MEDIA BIG BOOK DALAM MENINGKATKAN MINAT BACA SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS 5 SDI NW TANAH ABROR - Yuliana Asastri; Dewi Rohiani; Em.Thonthowi Jauhari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education plays a crucial role in enhancing the quality of human resources (HR) within a nation. However, Indonesia continues to face the problem of low reading interest among students, which negatively impacts their learning outcomes and overall competitiveness in the global era. This study aims to determine how the use of Big Book media can improve students’ reading interest in Grade V at SDI NW Tanah Abror. The research employs a qualitative descriptive method, involving observation, interviews, and documentation to collect data from 22 students and one teacher. The findings reveal that the use of Big Book media successfully increases students’ enthusiasm and motivation in reading activities. The colorful visuals, large fonts, and engaging illustrations within the Big Book make reading more enjoyable and interactive. Students actively participate in class discussions and demonstrate improved comprehension of the texts. Moreover, the frequency of library visits has increased since the implementation of Big Book–based learning. The study concludes that the Big Book is an effective medium to foster reading interest and literacy development among elementary school students. It not only enriches students’ learning experiences but also helps build a stronger reading culture within the school environment